p‐Graphene/Quantum Dot/n‐GaAs Mixed‐Dimensional Heterostructure Junction for Ultrathin Light‐Emitting‐Diodes - Quang Nhat Dang Lung; Rafael Jumar Chu; Eungbeom Yeon; Yeonhwa Kim; May Angelu Madarang; Won Jun Choi; Daehwan Jung (Advanced Materials Interfaces)
Abstract 2D materials such as graphene hold significant potential for optoelectronic applications due to their unique surface properties and strong light‐matter interaction. Despite the promise, achieving high‐performance photonic devices using 2D materials alone remains challenging, and therefore, integrating 2D materials with different dimensional semiconductors has emerged as an alternative approach to enhance device functionality. Here, p‐type graphene/InAs quantum dot (QD)/n‐type GaAs mixed‐dimensional heterojunctions are demonstrated for 1.3 µm light‐emitting diodes (LEDs) by using the p‐graphene as an ultrathin hole injection layer. These ultrathin hybrid devices show 800 × stronger electroluminescence output powers than the reference LEDs without p‐graphene. Energy band alignments at the heterojunction interface are also investigated by measuring UV photoemission spectroscopy to elucidate electrical characteristics. The novel hybrid 2D p‐graphene/0D QD/n‐GaAs light‐emitting diodes open up new ways for efficient ultrathin nanoscale light‐emitting optoelectronic devices.